Analisis Evaluasi Tata Kelola Aset Tetap Bumdes X Di Kabupaten Pasuruan - Mochamad Agung Setyabudi; Oktavendi, Tri Wahyu; Wicaksono, Agung Prasetyo Nugroho (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
The main problem of this research is that at the BUMDES X there are findings in the financial statements of BOMDES especially in the section of the financial position report not included the fair value of assets and the data of the value of fixed assets still using the nominal price of acquisition. This research uses a descriptive qualitative method approach, with data collection techniques: such as observation, data collection, processing, calculation, and analysis of various data. The results of this study show that: 1) The result of the calculation of assets remains bumdes does not need to be revalued, because all assets remain bumdes are still depreciated in the economic life calculation (still have residual book value) and only depression calculation each month with the linear method, 2) the book value on assets stays bumdes still there is a book value that can be included in the financial report especially the balance sheet, 3) in the administration of asset stays Bumdes still no pernumeration on the asset bumdes that adheres to the unit guidelines codification assets of the village according to the Directorate-General Building of the Government of the Village, Directorate of Financial Facilitations and Assets of Government of Village Year 2017